High out-of-pocket expenditure: making healthcare out-of-reach for lower income countries - Goel, Neha (International Journal of Psychosocial Rehabilitation, 2020)
Health care costs are rising worldwide. As per the WHO fact file, every year about 25 million households are pushed into poverty due to direct, out-of-pocket health payments. Key financing issue for low- and middle- income countries is how to provide increased financial protection for households. Reduction of economic and social inequality also has instrumental relevance for good health. Gross inequalities harm the health of the underdogs of society, both by undermining their lifestyles and by making them prone to harmful behavior patterns, such as smoking and excessive drinking. Lower income countries are prone to non-communicable diseases (NCDs) and growing aging population. Non-communicable diseases may be a result of globalization and urbanization which exposes them to risk-factors likeobesity, unhealthy lifestyle, consumption of alcohol or tobacco use. Public expenditure oh health is low in lower income countries and out-of-pocket expenditure is very high in these countries.Thus, people are pushed into poverty due to high health care costs in lower income countries.Models like integrated public healthcare or universal social health insurance system is the need of the hour. Well-designed policies and strategies are required to reduce OOP and its negative impacts. A healthy population can in turn help the economy to grow through increased efficiency and better pay. It is therefore a matter of urgency.